Regime shifts and uncertainty in pollution control - Aart de Zeeuw; Amos Zemel (Center for Economic Studies and ifo Institute (CESifo), 2012)
We develop a simple model of managing a system subject to pollution damage under risk of an abrupt and random jump in the damage coefficient. The model allows the full dynamic characterization of the optimal emission policies under uncertainty. The results, that imply prudent behavior due to uncertainty, are compared with the ambiguous outcomes reported in the literature for similar models. The differences are explained in terms of the properties of the damage function associated with each model. The framework is used to analyze the adaptation vs. mitigation dilemma and provides a simple criterion to determine whether adaptation activities should be undertaken promptly, delayed to some future date, or avoided altogether.
Keywords: Q28; Q52; Q54; 330; environmental pollution; optimal management; catastrophic transitions; uncertainty; adaptation; mitigation; Umweltpolitik; Mathematische Optimierung; Umweltbelastung; Risiko; Umweltschutz; Anpassung; Theorie